Kinematic Viscosity ofMulticomponent FeCuNbSiB-BasedMelts - Yuri N. Starodubtsev; Vladimir S. Tsepelev; Nadezhda P. Tsepeleva (Nanomaterials, 2021)
The work investigated the temperature dependences of the kinematic viscosity for multicomponent melts of nanocrystalline soft magnetic alloys. It is shown that there is a linear relationship between the reduced activation energy of viscous flow Ea·(RT)−1 and the pre-exponential factor ν0. This ratio is universal for all quantities, the temperature dependence of which is expressed by the Arrhenius equation. It is shown that the activation energy of a viscous flow is linearly related to the cluster size on a natural logarithmic scale, and the melt viscosity increases with decreasing cluster size. The change in the Arrhenius plot in the anomalous zone on the temperature dependence of viscosity can be interpreted as a liquid–liquid structure transition, which begins with the disintegration of clusters and ends with the formation of a new cluster structure.